NILAI-NILAI PENDIDIKAN PERTUNJUKAN WAYANG KULIT BALI LAKON BIMA MENCARI TIRTHA AMERTHA - Nyoman Astawan; I Ketut Muada; I Nyoman Sadwika (Widyadari, 2025)
Art of balinese puppet shadow perfarmances in Bali besides it is functioning religiously, its function as an education media. Therefore Balinese puppet shadow can be viewed as process of informal education which is very significant in understanding the value of attitude, mentality, ethies, and logic. In this context Dalang ( the puppet master) has a very imfartant and complext role which is a an artist, educator, religious expert, and philosopher, through Dalang artist. The puppet shadow performances, the community gets kuowledge about ethical valves, logic, atttitude and mentality. In general balinesa shadow pappet can provide educational value which is reflected through the family of pandawa.. The value of being praiseworthy reflected by the Rsi Drona and family Korawa. As such, the study used a descriptive-qualitative design, the data analyisis Bali shadow puppet show, particularly the case of Bima looking for holy water.